Eliciting preferences for public goods in non-monetized communities: Accounting for preference uncertainty - Andreas Pondorfer; Katrin Rehdanz (Kiel Institute for the World Economy (IfW), 2015)
One major challenge when conducting contingent valuation studies in developing countries is the choice of the appropriate payment vehicle. Since regular cash-income does not exist for the majority of the population and market integration is low, households in rural areas have less experience with monetary exchanges. In these cases labour time may be a more appropriate payment vehicle. A common finding of studies using labour time as the payment vehicle is that households are more often willing to contribute working time as compared to money. However, so far empirical evidence is missing if the labour time elicitation format reduces respondent's uncertainty of contributions. In this study we analyze and compare uncertainty of people's stated willingness to contribute (WTC) time and money for a local public good in a non-monetized small-scale community in Bougainville, Papua New Guinea. We do so by establishing an open-ended method for eliciting people's WTC, the Range-WTC-method, which elicits the upper and lower bound of a person's WTC. We find that uncertainty is reduced when respondents are asked for labour time contribution instead of monetary contributions. Thus, we provide empirical evidence that, indeed, labour time is the preferred to money in the elicitation of stated WTC in non-monetized communities.
Keywords: D81; Q51; Q56; 330; Contingent valuation; Non-monetized community; Payment vehicles; Preference uncertainty